Pemikiran Munawir Sjadzali dan relevansinya di era disrupsi - Muhroni, Tedy (Maliki Interdisciplinary Journal, 2025)
Along with the development of the times, various kinds of thoughts about the renewal of Islamic law began to emerge. Munawir Sjadzali is one of the Muslim intellectuals who initiated thoughts on the reactualisation of Islamic law as a response to the many scholars and intellectual figures who lacked the courage to convey their thoughts which resulted in the decline of Islam. Munawir Sjadzali’s ideas on the reactualisation of Islamic law focus on the issues of inheritance and bank interest and the relevance of his thoughts in the era of disruption with all the dynamics in it. Munawir Sjadzali’s ideas in the reactualisation of Islamic law regarding the issue of inheritance, Munawir Sjadzali argues that the division of inheritance between men and women must be the same, namely 1:1, based on the principle of gender equality and a gradual system in Islam. In addition, regarding bank interest, Munawir Sjadzali argues that bank interest is allowed as long as no party is harmed. This opinion is based on the high need of the community for banking services and the view that the use of bank services provides more benefits in the present context.